(untitled) (Modern Problems of Metallurgy, 2022)
The paper aims to research performance evaluations of a multiprocessor system in the problem of metal heat treatment. The research aims at the performance evaluations of a multiprocessor computer system. That reveals the problem of matching the computing capabilities of multiprocessor system processors with this system network interface. On the example of solving the problem of metal products heat treatment, analytical relations are derived to determine the optimal number of nodes of the cluster system according to the selected processors. The values of the consistency coefficient of the selected processors' capabilities, the network interface, and the size of the computing domain are derived. Estimates of cluster system performance at solving the metal heat treatment problem for various processors’ classes are defined.